2019
DOI: 10.2139/ssrn.3414012
|View full text |Cite
|
Sign up to set email alerts
|

The Stability of Irradiation-Induced Defects in Zr <sub>3</sub>AlC <sub>2</sub>, Nb <sub>4</sub>AlC <sub>3</sub> and (Zr <sub>0.5</sub>,Ti <sub>0.5</sub>) <sub>3</sub>AlC <sub>2</sub> Max Phase-Based Ceramics

Abstract: Publisher's PDF, also known as Version of record Cyswllt i'r cyhoeddiad / Link to publication Dyfyniad o'r fersiwn a gyhoeddwyd / Citation for published version (APA): a b s t r a c tThis work is a first assessment of the radiation tolerance of the nanolayered ternary carbides (MAX phases), Zr 3 AlC 2 , Nb 4 AlC 3 and (Zr 0.5 ,Ti 0.5 ) 3 AlC 2 , using proton irradiation followed by post-irradiation examination based primarily on x-ray diffraction analysis. These specific MAX phase compounds are being evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…103,104 Furthermore, Zr-and Nb-based MAX phases have been recently considered due to the small neutron cross-section of Zr and the favorable refractory metal properties of Nb. 105 The post-irradiation examination revealed that Zr 3 conditions due to the preference for M:A antisites and C Frenkel pairs at the M-2 layer. 105…”
Section: Radiation Tolerancementioning
confidence: 96%
“…103,104 Furthermore, Zr-and Nb-based MAX phases have been recently considered due to the small neutron cross-section of Zr and the favorable refractory metal properties of Nb. 105 The post-irradiation examination revealed that Zr 3 conditions due to the preference for M:A antisites and C Frenkel pairs at the M-2 layer. 105…”
Section: Radiation Tolerancementioning
confidence: 96%
“…The MAX phase is named after its distinct layered structure and chemical composition, where M is an early transition metal, A represents an A-group element, and X can be carbon and nitrogen. The solid covalent bonding between M and X endows MAX phase with high elastic modulus, [6][7][8][9][10] outstanding damage tolerance, 11,12 certain mechanical properties, [13][14][15] and the high partial density of states (PDOS) value of the M elements at the Fermi level gives the MAX phase extra electrical conductivity. 16,17 The relatively weak interaction between MX and A makes A layers easily be etched by oxidizing acids or salts, leading to the emergence of a new series of two-dimensional materials named MXene.…”
Section: Introductionmentioning
confidence: 99%